2019
DOI: 10.3102/0002831219890300
|View full text |Cite
|
Sign up to set email alerts
|

Digital Versus Paper Reading Processes and Links to Comprehension for Middle School Students

Abstract: This study explores digital and paper reading processes and outcomes for 371 fifth to eighth graders completing a reading task similar to standardized testing. Results showed students highlighted and annotated more when reading the paper versus digital text. Also, reading on paper versus digitally was slightly supportive of reading comprehension for the longer section of text. For behaviors, digital highlighting and looking back at the paper text were supportive of reading comprehension, whereas paper highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 42 publications
0
32
0
3
Order By: Relevance
“…Se encontraron resultados contradictorios al comparar la lectura en textos digitales e impresos. En este grupo de estudios, Goodwin et al (2020) hallaron que las anotaciones en papel y digitales, sumado al uso de diccionarios en línea y el subrayado digital no se vincularon a la comprensión lectora. Así mismo, Alisaari et al (2018) señalan que, independientemente del medio de lectura, los estudiantes comprenden igual con libros y computadoras, es decir, el rendimiento fue similar para el texto impreso y digital texto.…”
Section: Resultados Discretos Y Menos Significativosunclassified
See 1 more Smart Citation
“…Se encontraron resultados contradictorios al comparar la lectura en textos digitales e impresos. En este grupo de estudios, Goodwin et al (2020) hallaron que las anotaciones en papel y digitales, sumado al uso de diccionarios en línea y el subrayado digital no se vincularon a la comprensión lectora. Así mismo, Alisaari et al (2018) señalan que, independientemente del medio de lectura, los estudiantes comprenden igual con libros y computadoras, es decir, el rendimiento fue similar para el texto impreso y digital texto.…”
Section: Resultados Discretos Y Menos Significativosunclassified
“…Algunos estudios hicieron comparaciones directas entre las bondades del texto digital y el texto impreso en la comprensión lectora (Alisaari et al, 2018;Calle & Gómez, 2020;Danaei et al, 2020;Goodwin et al, 2020;Long & Szabo, 2016;Wainwright et al, 2020). Otros contrastaron los efectos del texto digital lineal y el texto digital con hipertextos en la lectura (Blom et al, 2019;Soria, 2015aSoria, , 2015b.…”
Section: Tipos De Textos Digitales Y Tecnologías Utilizadasunclassified
“…New studies also show simple differences between two more basic modalities of reading: static texts (e.g., PDFs) presented on screens and those printed on paper. Research comparing static texts presented on screen versus on paper suggests profound differences in both reading behavior (e.g., Goodwin et al, 2019) and reading comprehension outcomes, with meta‐analyses suggesting the superiority of paper comprehension (e.g., Clinton, 2019; Delgado et al, 2018). With many teachers planning for remote or hybrid learning environments for the fall due to the COVID‐19 pandemic, teachers must be aware of the affordances and constraints of both paper and digital literacies.…”
Section: Going Beyond the Guide’s Recommendationsmentioning
confidence: 99%
“…Although offline and online reading overlap in many ways, research has suggested that they are not the same. This appears to be the case in less complex contexts, such as when reading on paper is compared with reading the same text on a screen without hyperlinks or other dynamic features (Goodwin et al, 2019). For example, Goodwin et al (2019) found that highlighting was correlated negatively with comprehension in a paper context but positively in a screen context, and suggested that this may point to the increased importance of strategic behaviors in digital contexts.…”
Section: Theoretical and Empirical Perspectivesmentioning
confidence: 99%
“…Research has suggested that motivation may function somewhat differently online for several reasons. First, although offline and online reading share many similar characteristics, empirical results suggest that they are not the same (Afflerbach & Cho, 2009; Coiro, 2011; Coiro & Dobler, 2007; Goodwin, Cho, Reynolds, Brady, & Salas, 2019). Online contexts may require greater attention to locating, evaluating, and self‐monitoring (B.‐Y.…”
mentioning
confidence: 99%